Outcomes of High Kidney Donor Profile Index Hepatitis C Nucleic Acid Testing Positive Kidneys are Equivalent to Matched Hepatitis C Nucleic Acid Testing Negative Kidneys - Shengliang He, MD; Christie P. Thomas, MD; Alan E. Gunderson, MD; Patrick Ten Eyck, PhD; Alan I. Reed, MD, MBA (Transplantation Direct)
Background. A recent Organ Procurement and Transplant Network policy change removes hepatitis C virus (HCV) status and race from the Kidney Donor Profile Index (KDPI) calculation, thereby lowering the KDPI of HCV nucleic acid testing positive (NAT+) kidneys and increasing their allocation priority. However, even in the era of direct-acting antivirals, high KDPI HCV NAT+ kidneys exhibited higher discard rates compared with their HCV NAT– counterparts, and outcome data for this “high-risk” group remain limited. This study aims to address this knowledge gap by providing comprehensive outcome data to better inform organ allocation and selection decisions under the new KDPI framework. Methods. Using national transplant data from 2015 to 2023, we analyzed adult deceased donor kidney transplants stratified by KDPI and HCV NAT status. An exact matching model was used to identify the matched HCV NAT– group. Results. No significant differences were observed in delayed graft function, rejection, or patient and graft survival between high KDPI HCV NAT+ and matched HCV NAT– recipients. High KDPI HCV NAT+ kidneys were more often allocated regionally or nationally, with 67.6% occurring in 4 regions. Their recipients were more likely to have a high school education and shorter wait times. After the policy change, >90% of prior high KDPI HCV NAT+ kidneys will no longer be classified as high KDPI. Conclusions. Our findings support the safe utilization of previously high KDPI HCV NAT+ kidneys after a policy change. Although the revised KDPI may assist clinicians in identifying higher-quality organs, its impact on existing sociodemographic disparities and overall organ utilization rate remains uncertain.